Comparison of Zinc, Copper and Selenium Content in Raw, Smoked and Pickled Freshwater Fish - Konrad Mielcarek; Anna Puścion-Jakubik; Krystyna J. Gromkowska-Kępka; Jolanta Soroczyńska; Elżbieta Karpińska; Renata Markiewicz-Żukowska; Sylwia K. Naliwajko; Justyna Moskwa; Patryk Nowakowski; Maria H. Borawska; Katarzyna Socha (Molecules, 2020)
The aim of the study was to assess the zinc (Zn), copper (Cu) and selenium (Se) content in freshwater fish from Poland. Selected species of raw, smoked and pickled fish were evaluated by atomic absorption spectrometry (AAS). The concentration of Zn, Cu and Se in the examined fish ranged from 1.5 to 49.9 mg/kg, 0.01 to 2.8 mg/kg and 30.9 to 728.2 µg/kg, respectively. One serving of every fish product covered the recommended dietary allowance (RDA) of Zn by 5.38–65.0%, of Cu by 0.42–11.4% and of Se by 12.3–198.6%. A cluster analysis allowed us to distinguish European eel (raw and smoked) based on the Zn content. Additionally, based on the Cu and Se content, pickled common whitefish was differentiated from other species and types of fish products. The discriminant analysis model of smoked fish enabled their classification with a 70% accuracy. Regarding Zn, all forms of the European eel as well as raw and smoked vendace can be considered a source of this element. None of the tested fish can be considered a source of Cu. All products are safe for human consumption with regard to the Zn and Cu content. Almost each form of every species of fish can be considered a source of Se. However, the Se content should be monitored in smoked and pickled common whitefish, pickled bream and pickled vendace.